Immanent Frames: Postsecular Cinema Between Malick and Von Trier - Caruana, John (SUNY Series, Horizons of Cinema Ser, 2018)
Intro -- Contents -- Illustrations -- Acknowledgments -- What Is Postsecular Cinema? An Introduction -- Notes -- Part I: The Poles of Postsecular Cinema: Malick and von Trier -- 1 Two Ways through Life: Postsecular Visions in Melancholia and The Tree of Life -- Transcendence and Immanence: The Tree of Life and Melancholia -- The Way of Transcendence: The Tree of Life -- The Way of Immanence: Melancholia -- The "Affective Sublime" -- Notes -- Bibliography -- 2 Hegel, Malick, and the Postsecular Sublime -- The Hegelian Sublime -- Symbolic Art-Form -- Symbolism of the Sublime -- Art of the Sublime -- Truth and the Sublime -- Art, Religion, and Philosophy -- Contemporary Art of the Sublime -- The Tree of Life -- Fragmented Narrative -- Hermeneutic Sublimation -- The Postsecular Sublime -- Notes -- 3 Repetition and Belief: A Kierkegaardian Reading of Malick's The Tree of Life -- Kierkegaard: The Missing Third in Malick's Philosophical Triad -- Repetition and Belief in Malick's The Tree of Life -- Notes -- 4 Toward and Away from the World: Subjectivity After Loss in The Tree of Life -- Notes -- 5 The Death of God and the Genesis of Worldhood in von Trier's Melancholia -- The End of the Secularist World -- Resurrecting the Death of God -- Creation ex nihilo -- Notes -- 6 Notes on Divine Homelessness: A Reading of Lars von Trier's Dogville -- Theologia ludens -- A (Trick-)Playing God -- A Homeless God -- The Politics of Despair -- Notes -- Bibliography -- Part II: The Spectrum of Postsecular Cinema: Beyond Malick and von Trier -- 7 Face to Face with Chantal Akerman -- Notes -- 8 "There's No Point in Killing a Bad Priest": John Michael McDonagh's Calvary and the Broken Middle -- Introduction -- Film and Religion between Immanence and Transcendence -- The Broken Middle -- Christianity, Mythology, and the Cosmological -- Calvary: A Film Maudit? -- Notes